Exceptional diversity of Tischeriidae (Lepidoptera) from a single tropical forest site in Belize, Central America - Stonis, JR; Diškus, A; Remeikis, A; Lewis, OT (Consortium of European Natural History Museums, 2020)
We report on fourteen species and four genera of Tischeriidae recorded from Las Cuevas, a single tropical forest locality in Belize, Central America. This is the highest number of species of Tischeriidae recorded from a single locality worldwide, exceeding the species and generic diversity of the entire Tischeriidae fauna of Europe and accounting for about 9% of the documented global fauna for this family. We describe and name six new species: Astrotischeria papilloma Diškus & Stonis sp. nov., mining on Lasianthaea fruticosa (L.) K.M.Becker (Asteraceae); A. scutifera Diškus & Stonis sp. nov., mining on Sida glabra Mill. (Malvaceae); A. basilobata Remeikis & Stonis sp. nov., mining on Lasianthaea fruticosa; Paratischeria robinsoni Diškus & Stonis sp. nov., mining on Otopappus verbesinoides Benth. (Asteraceae); P. tubifex Diškus & Stonis sp. nov., mining on Lasianthaea fruticosa; and P. belizensis Remeikis & Stonis sp. nov. (host plant unknown). Additionally, we review eight previously described species from the same period of collecting at Las Cuevas in 1997–1998: A. selvica Diškus, Carvalho-Filho & Stonis, 2018, mining on Sphagneticola trilobata (L.) Pruski and Synedrella nodiflora (L.) Gaertn. (Asteraceae); A. casila Diškus & Stonis, 2018, mining on Montanoa atriplicifolia (Pers.) Sch.Bip. (Asteraceae); A. furcata Diškus & Stonis, 2018 (host plant unknown); Paratischeria neotropicana (Diškus & Stonis, 2015), mining on Sida L. (Malvaceae), including S. rhombifolia L.; Dishkeya gouaniae (Stonis & Diškus, 2007), mining on Gouania polygama (Jacq.) Urb. (Rhamnaceae); Coptotriche pulverea (Walsingham, 1897), mining on Terminalia amazonia (J.F.Gmel.) Exell (Combretaceae); C. forsteroniae Stonis & Diškus, 2008, mining on Forsteronia myriantha Donn Sm. (Apocynaceae); and C. singularis Stonis & Diškus, 2008 (host plant unknown). All taxa, except for C. singularis, are illustrated with photographs of the adults and their genitalia. We also briefly discuss the discovery of some novel characters for Astrotischeria Puplesis & Diškus, 2003 and Paratischeria Diškus & Stonis, 2017, Tischeriidae, and provide the first photographic documentation of Coptotriche pulverea and C. forsteroniae.